2008
DOI: 10.1016/j.neuroscience.2008.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression and localization of hippocampal A-type potassium channel subunits in the pilocarpine-induced model of temporal lobe epilepsy

Abstract: SummaryAltered ion channel expression and/or function may contribute to the development of certain human epilepsies. In rats, systemic administration of pilocarpine induces a model of human temporal lobe epilepsy, wherein a brief period of status epilepticus (SE) triggers development of spontaneous recurrent seizures that appear after a latency of two-three weeks. Here we investigate changes in expression of A-type voltage-gated potassium (Kv) channels, which control neuronal excitability and regulate action p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 64 publications
1
64
1
Order By: Relevance
“…Bernard et al [15] also showed that the amplitude of backpropagating action potentials was increased in CA1 pyramidal cell dendrites in pilocarpine-induced temporal lobe epilepsy, suggesting decreased functional expression of dendritic Kv4 channels and Monaghan et al [16] showed that Kv4.2 in CA1 stratum radiatum and Kv4.3 in the molecular layer of the dentate gyrus decreased 12 weeks post-status epilepticus compared with the control animal, and KChIP was lost in interneurons throughout the dentate gyrus 4 weeks post-status epilepticus. They also demonstrated that Kv4.2 mRNA expression was present in cerebellum, hippocampus, medial habenula, cerebral cortex, and thalamus and there was significant downregulation of Kv4.2 mRNA in dentate granule cells of hippocampus following seizure activity induced by convulsant drug pentylenetetrazole treatment through an unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Bernard et al [15] also showed that the amplitude of backpropagating action potentials was increased in CA1 pyramidal cell dendrites in pilocarpine-induced temporal lobe epilepsy, suggesting decreased functional expression of dendritic Kv4 channels and Monaghan et al [16] showed that Kv4.2 in CA1 stratum radiatum and Kv4.3 in the molecular layer of the dentate gyrus decreased 12 weeks post-status epilepticus compared with the control animal, and KChIP was lost in interneurons throughout the dentate gyrus 4 weeks post-status epilepticus. They also demonstrated that Kv4.2 mRNA expression was present in cerebellum, hippocampus, medial habenula, cerebral cortex, and thalamus and there was significant downregulation of Kv4.2 mRNA in dentate granule cells of hippocampus following seizure activity induced by convulsant drug pentylenetetrazole treatment through an unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…By severely dampening dendritic excitability, I A influences dendritic integration and propagation of information and modulates the input and output relationship of electrical signals. Reductions in the Kv4.2 channel mRNA or protein level have been demonstrated in animal models of epilepsy (5)(6)(7)(8). A mutation in KCND2, the gene encoding Kv4.2, was found in a patient with temporal lobe epilepsy (9).…”
mentioning
confidence: 99%
“…NMDA receptor activation not only transiently reduces Kv4.2 protein level due to degradation, but also increases Kv4.2 protein production in a fragile × mental retardation protein-dependent process likely involving Kv4.2-3 ′ UTR (Lei et al 2010;Lee et al 2011). Furthermore, deficits in spatial memory and context discrimination are associated with a reduction of Kv4.2 channel phosphorylation (Morozov et al 2003), whereas reduction in surface expression of Kv4.2 channels parallels impairments in spatial memory in status epilepticus (Lugo et al 2008;Monaghan et al 2008). Recently, Lockridge and Yuan (2011) showed that Kv4.2 knockout mice are impaired in a spatial learning task.…”
mentioning
confidence: 99%